Principal Leadership Strategy in Troubled Times: Studies at SMK Muhammadiyah Purwodadi Purworejo - Eko Nurrahmad; Muhammad Sayuti; Edhy Susatya (Journal of Vocational Education Studies, 2023)
The objectives of this study are (1) to find the challenges faced by SMK in difficult times to transform into advanced vocational schools; (2) analyze the principal's leadership strategy in transforming schools in difficult times into advanced vocational schools;  (3) analyze the leadership character of the head of SMK Muhammadiyah Purwodadi Purworejo in transforming schools in difficult times into advanced vocational schools. The research uses a qualitative approach with a best practice model.  The research was conducted at SMK Muhammadiyah Purwodadi Purworejo. Data collection was carried out using semi-structured interview techniques.  Data analysis was carried out using the thematic approach of Braun and Clark model analysis  which includes six steps, namely becoming familiar with the data, generating initial codes, searching for themes, review themes, define themes and write up. The results showed that (1) the conditions in the difficult times experienced by SMK Muhammadiyah Purwodadi were limited teachers, small and unpaid students, financial limitations, limited facilities and infrastructure, poor school reputation and competition with other schools.  (2) The leadership strategy implemented by the Head of SMK Muhammadiyah Purwodadi in transforming schools in difficult times into advanced schools is carried out by increasing the number of students, building networks with various parties and all stakeholders, improving the quality and capacity of teachers, improving the image of the school or rebranding to change  the image of the  school and improving facilities and infrastructure .  (3) The leadership character of the head of SMK Muhammadiyah Purwodadi in transforming a school in difficult times into an advanced school is reflected in the thinking behavior of future oriented, creative, innovative and communicative, optimistic and daring to take risks, hard work, never give up and motivate, fast, charismatic and exemplary, empathy, observant of opportunities, religious and have a sense of ownership.